Taisīr An-Naḥwi al Ta’līmī lī Garḍ Qirāati An-Nuṣūṣ Al-‘Arabiyyah Gair al-Masykūlah - Ade Arip Ardiansyah; Aji Abdul Aziz (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
Taisīr An-Naḥwi al Ta’līmī lī Garḍ Qirāati An-Nuṣūṣ Al-‘Arabiyyah Gair al-MasykūlahAde Arip Ardiansyah, Aji Abdul AzizIslamic State University of Sunan Gunung Djati BandungAdearipardiansyah94@gmail.com, aziealmaraby@gmail.comAbstractThis research aims at describing the grammatical difficulties faced by the students of the Faculty of Islamic Studies at the University of Muhammadiyah Bandung in reading the unconventional Arabic texts. The attempt by the Faculty of Islamic Studies at the University of Muhammadiyah Bandung is to facilitate the educational method for reading non-Arabic texts. The researcher chose the qualitative approach in the research using the methods of observation and interview for data collection, and the analytical method of analysis of the analysis of Miles and Huberman. The results of the research showed that the grammatical difficulties faced by the students of the Faculty of Islamic Studies at the University of Muhammadiyah Bandung varied from lack of understanding in the concepts of word, compound and sentence, which are essential in the study of grammatical science, and that the facilitation of the educational method carried out by Islamic studies at Muhammadiyah Bandung University, Grammatical and simplistic analysis where the theory of rhetoric and descriptive analysis was used in the analysis of sentence.Keyword: Facilitation of grammar, Reading texts, Arabic.تيسير النحو التعليمي لغرض قراءة النصوص العربية غير المشكولةأدي عاريف أرديانشه، أجي، عبد العزيزAdearipardiansyah94@gmail.com, aziealmaraby@gmail.comالملخص استهدف هذا البحث إلى وصف الصعوبات النحوية التي واجهها طلبة كلية الدراسات الإسلامية بالجامعة المحمدية باندونج في قراءة النصوص الع ربية غير المشكولة، ووصف المحاولة التي قامت بها كلية الدراسات الإسلامية بالجامعة المحمدية باندونج في تيسير النحو التعليمي لغرض قراءة النصوص العربية غير المشكولة. واختار الباحث المدخل النوعي في البحث مستخدما أساليب الملاحظة والمقابلة لجمع البيانات، وأسلوب التحليل التفاعلي لماليز وهوبيرمان لتحليلها. ودلت نتائج البحث أن الصعوبات النحوية الي واجهها طلبة كلية الدراسات الإسلامية بالجامعة المحمدية باندونج متنوعة مصدرها من عدم الفهم في مفاهيم الكلمة والمركب والجملة وهي مواد أساسية في دراسة علم النحو، وأن تيسير النحو التعليمي الذي قامت به الدراسات الإسلامية بالجامعة المحمدية باندونج سارت على شكل إعادة تنسيق المواد النحوية وتبسيط التحليل حيث استخدمت نظرية علم البلاغة والتحليل الوصفي في تحليل الجملة.الكلمة الرئيسية: تيسير النحو، قراءة النصوص، العربية.